The Role of Technology and Environment in E-Commerce Adoption among MSMEs in Semarang City - Ayuwardani, Mellasanti; Ristianti, Meira Dwi; Sulistiyani, Endang; Sandriatwati, Sri Eka; Rustono, Rustono; Utaminingtyas, Rara Ririn Budi; Mirrah, Irin (RSF Conference Series: Business, Management and Social Sciences, 2025)
The rapid advancement of technology has enabled individuals to conveniently perform various activities anytime and anywhere, such as exchanging data and information, communicating with others, and engaging in buying and selling transactions without geographical or temporal constraints. This study adopts an explanatory research design. The research population comprises micro-scale MSMEs located in the city of Semarang. The study employed purposive sampling, resulting in a sample size of 41 respondents. A quantitative method was adopted, with questionnaires serving as the primary instrument for gathering data, which were then processed using IBM SPSS version 25. The findings reveal that both technological and environmental factors, individually and collectively, exert a significant influence on e-commerce adoption, accounting for 43.8% of the variance.